Multiple metastases of androgen indifferent prostate cancer in the urinary tract: two case reports and a literature review - Tsukasa Masuda; Takeo Kosaka; Kohei Nakamura; Hiroshi Hongo; Kazuyuki Yuge; Hiroshi Nishihara; Mototsugu Oya (BMC Medical Genomics, 2022)
Abstract Background Prostate cancer (PC) is mainly known to metastasize to bone, lung and liver, but isolated metastases of prostate cancer, including ductal carcinoma, in the urinary tract are very rare. We describe two patients with nodular masses in the urinary tract (the anterior urethra or the urinary bladder) that were found on cystoscopy during treatment of castration-resistant prostate cancer. Case presentation In both cases, the pathological diagnosis from transurethral tumor resection showed that they were androgen indifferent prostate cancer (AIPC), including aggressive variant prostate cancer (AVPC) in Case 1 and treatment-induced neuroendocrine differentiation prostate cancer (NEPC) in Case 2. In Case 1, Loss of genetic heterozygosity (LOH) of BRCA2 and gene amplification of KRAS was identified from the urethra polyps. In Case 2, homozygous deletion was observed in PTEN, and LOH without mutation was observed in RB1. Conclusion These are the first reports of two cases of urinary tract metastasis of AIPC.